The effect of peer support on quality of life among type 2 diabetic patients in deprived areas in Iran: A randomized clinical trial - Arezoo Shahsavari; Fatemeh Estebsari; Foroozan Atashzadeh-Shoorideh; Mahnaz Ilkhani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Quality of life (QOL) is one of the effective factors in promoting the health of diabetic patients. In recent years, the role of peer support in the optimal management of diabetes has gained increasing attention. However, contradictory results have been reported from the effectiveness of this method. This study aimed to investigate the effect of peer support on the QOL among type 2 diabetic patients in deprived areas. MATERIALS AND METHODS: This study was a randomized clinical trial conducted on 80 patients with T2D referring to the diabetes Clinic in Aligoudarz in Iran. Participants were randomly assigned into two groups of 40 patients. Intervention group received a peer Supportive-educational program for 3 months and the control group received routine clinic care. Diabetes QOL brief clinical inventory was used to collect the data. This questionnaire was completed three times at the beginning of the study, immediately after the 3-day training, and after 3 months of peer supportive intervention. The SPSS software (v. 18.0) was used to analyze the data through the Generalized Estimating Equations. RESULTS: There was no significant difference in mean QOL between the two groups before the intervention (P = 0.891) and immediately after the education (P = 0.076). However, after 3 months of intervention, the intervention group showed a significant improvement in mean QOL compared to those in the control group (P < 0.001). CONCLUSION: Peer support program can improve the QOL in type 2 diabetic patients in deprived areas. Therefore, this method can be recommended to improve care and educational programs in these patients.